To Pad or Not to Pad: Towards Better Sanitary Care for Women in Indian Slums. (January 2017) - Garikipati, Supriya; Boudot, Camille
Abstract: A number of programmes have recently been initiated to popularise the use of sanitary pads among poor women in developing countries. In this light, we review the prevailing menstrual practices in different contexts across India, as well as the initiatives undertaken to improve sanitary care. We also report findings from a study amongst women in slums of Hyderabad. We find high usage of sanitary pads (56 to 64 percent), suggesting that development initiatives have percolated down to the urban poor. Furthermore, we find that although a large number of cloth users (57 percent) are willing to change practice, an overwhelming number of them (94 percent) elicit a preference for re‐usable cloth pads. This suggests a disengagement with public policy discourses on menstrual care that have so far focused singularly on promotion of sanitary pads. We draw upon these results to comment on better sanitary care for women slum dwellers in a rapidly urbanising context. Copyright © 2017 John Wiley & Sons, Ltd.